Behavioural research for marketing : a practitioner's handbook - Adams, Julian (Researcher on marketing) (New York, NY : Routledge, 2022)
"This book, the first of its kind, provides market researchers and marketeers with the tools to better understand human behaviour by drawing upon social science theory from different schools of thought, including sociology, psychology and behavioural economics. It has practical examples throughout to help illustrate how to operationalise theory in market research and to underpin the way we understand how people think, behave, decide and make the choices. Each theory is explained in accessible terms to ensure that the content is relevant and useful to commercial market researchers. By considering different theoretical models of human behaviour from the outset, this book will open new avenues of investigation, develop more dynamic and challenging hypotheses to test during the research process, and ultimately result in more insightful outcomes. The book brings together theories that look at how society is shaped and formed, how this impacts on the individual, along with theories that focus on the mind and behaviour of the individual; these perspectives are equally important in market research but not usually considered within the same text. This book is not limited to theory alone, in each chapter, illustrative examples are used to help demonstrate how theory can be applied to real world market research projects. Additionally, throughout there are helpful suggestions in terms of question content to help operationalise theory. This book will appeal to the university graduates that have recently entered the field of market research and are interested in the theoretical underpinnings of human behaviour, undergraduates and post-graduates that are studying marketing, business studies or social science, where a core component of the course requirement is market research and finally those that are users of market research data and want a working knowledge of key theories of human behaviour"--
Keywords: Marketing -- Research; Marketing -- Psychological aspects; Behaviorism (Psychology) -- Social aspects; Marketing research; BUSINESS & ECONOMICS / Marketing / Research; BUSINESS & ECONOMICS / Marketing / Multilevel; PSYCHOLOGY / Social Psychology